FEATURES OF THE CLINICAL COURSE OF PERIODONTAL DISEASES IN PATIENTS WITH GASTRIC AND DUODENAL ULCER WITH FIXED DENTURES - Dvornyk, V.M.; Roshchuk, О.І.; Belikov, O.B.; Havaleshko, V.P.; Karavan, Ya.R.; Khukhlina, O.S. (World of Medicine and Biology, 2023)
The examination of periodontal tissues in patients with gastric and duodenal ulcers with the presence of fixed dentures has been studied. The purpose of the study was to establish the frequency and features of the clinical course of periodontal disease at the presence of fixed dentures. It was established that the prevalence of periodontal disease in patients with gastric and duodenal ulcers without dental prosthetics is determined in 86.2 % of people, and at the presence of fixed dentures – in 100 % of people. The highest number of cases of chronic generalized periodontitis of I and II degree of severity was found in the group of patients with fixed metal dentures (60.0% and 29.2% of people, respectively), which was in 1.6 times and 2.6 times respectively higher in patients with fixed ceramic dentures (p
Keywords: periodontal disease; gingivitis; gastric and duodenal ulcer; fixed metal dentures; ceramic dentures